Low sintering temperature enhancing colossal dielectric permittivity and humidity sensitivity in Ta5+ substituted TiO2 ceramics via high energy ball milling - Chotchaya Phianjing; Nutthakritta Phromviyo; Navadecho Chankhunthod; Pornjuk Srepusharawoot; Pairot Moontragoon; Prasit Thongbai (Scientific Reports)
Abstract Nanostructured 1% and 10% Ta5⁺-substituted TiO2 (TTO) ceramics were synthesized via high-energy ball milling and sintered at 1200 °C and 1300 °C to investigate their dielectric and humidity sensing performance. XRD confirmed a single-phase rutile TiO2 structure in both the powdered and sintered ceramics, while SEM and EDS analyses revealed dense microstructures with nanoscale grains and uniform Ta5⁺ dispersion, particularly at the lower sintering temperature. The 10%TTO ceramic sintered at 1200 °C exhibited colossal dielectric permittivity (ε′ ≈ 1.3 × 105) with a relatively high loss tangent, whereas both 1%TTO and 10%TTO sintered at 1300 °C achieved similarly high ε′ values with significantly reduced dielectric loss (tan δ ≈ 0.026 at 1 kHz). Excellent thermal stability was maintained, with Δε′ <  ± 15% and tan δ < 0.1 up to 200 °C. Furthermore, ceramics sintered at 1200 °C demonstrated outstanding humidity sensing behavior, including high linearity, low hysteresis (γHmax = 3.0%), and rapid response/recovery times (3.0/0.5 min). These exceptional properties are attributed to the nanoscale microstructure and defect-mediated intrinsic factors at the ceramic surface. The synergy of colossal dielectric permittivity, excellent temperature stability, and superior humidity sensitivity highlights the potential of Ta5⁺-substituted TiO2 ceramics as promising candidates for advanced capacitors and humidity sensors, with performance tunable by sintering conditions.